Analysis of Business Process Management (BPM) Effect towards Data and Information Quality Improvement at Higher Education: A Literature Study - Sujanawati, Risa Perdana; ER, Mahendrawathi; Wibowo, Radityo Prasetianto (IPTEK The Journal for Technology and Science, 2025)
Business Process Management (BPM) is a collection of methods, techniques, and tools to optimize organizational performance. In the case of higher education institutions (HEIs), BPM is usually implemented to provide a standard business process. Implementation of Data Governance (DG) is often based on the desire for good Data Quality (DQ), to help an organization carry out its strategies and achieve its objectives. Previous research has proven that DG would improve data quality and safety and trigger a better standard. While data and information are essentially connected, BPM and DG have been addressed separately in the process of obtaining high quality data and information. This study conducts a literature review to investigate the relationship of BPM in the development of DG in HEIs. Articles related to BPM, DG, and DQ are collected from relevant databases. The articles are filtered and perused further to obtain 23 articles that are analyzed and synthesized to answer the research question. Based on these articles, a conceptual model is developed, depicting relationship in the application of BPM and DG. The first relationship identified from previous work is that the successful implementation of BPM influences DG planning and implementation success. Second, a good BPM implementation influences the process of obtaining a good DQ. Finally, implementing a good DG influences the acquirement of a good DQ. This study also found that BPM, DG, and DQ implementation at HEIs was fewer than that at other sectors or case studies, which open up opportunities for further studies.